Determinants of Breast Self-Examination (BSE) on Female Adolescents in Kupang City - Elen A. R. P Ataupah; Engelina Nabuasa; Helga J. N. Ndun (Universitas Nusa Cendana, 2023)
Breast self-examination (BSE) is one method of early detection of breast cancer that women themselves can do. BSE was necessary because the suffering could find 85% of lumps in the breast, but many women still did not understand what BSE was and how its practice. This study aimed to determine the determinants of BSE in female adolescents in Kupang City. This type of research was quantitative with a cross-sectional study design. This research was conducted in Kupang City with 381 young women. The data analysis used was univariate and bivariate analysis with a chi-square statistical test. The results showed that there was a relationship between knowledge (ρ-value = 0.030), attitudes (ρ-value = 0.000), information exposure (ρ-value = 0.000), parental support (ρ-value = 0.000), and peer support (ρ-value= 0.000) on breast self-examination (BSE). Female adolescents were expected to be active in seeking information related to BSE and be able to do BSE regularly according to the rights steps. It was also hoped that the Kupang City Health Office would increase health promotion efforts by utilizing various media, especially counseling/socialization about BSE.